Zinc Oxide Nanoparticles Catalyzed Condensation Reaction of Isocoumarins and 1, 7-Heptadiamine in the Formation of Bis-Isoquinolinones. (12th March 2012) - Krishnakumar, Varadhan; Mohan Kumar, Kesarla; Mandal, Badal Kumar; Khan, Fazlur-Rahman Nawaz
Abstract : The diversified bis-isoquinolinones were obtained in two steps, utilizing homophthalic acid and various acid chlorides providing 3-substituted isocoumarins in the first step which on further condensation with 1, 7-heptadiamine involving C–N bond formation from the lactone in the presence of 10 mol% zinc oxide nanoparticles (ZnO NPs) (<150 nm) afforded the desired bis-isoquinolinones in high yield and purity. The synthesized compounds were then characterized using FTIR, 1 H NMR, 13 C NMR, and HRMS techniques.